NiCoFe‐Layered Double Hydroxides/N‐Doped Graphene Oxide Array Colloid Composite as an Efficient Bifunctional Catalyst for Oxygen Electrocatalytic Reactions. Issue 9 (8th December 2017) - Zhou, Daojin; Cai, Zhao; Lei, Xiaodong; Tian, Weiliang; Bi, Yongmin; Jia, Yin; Han, Nana; Gao, Tengfei; Zhang, Qian; Kuang, Yun; Pan, Junqing; Sun, Xiaoming; et al.
Abstract: Ternary NiCoFe‐layered double hydroxide (NiCo III Fe‐LDH) with Co 3+ is grafted on nitrogen‐doped graphene oxide (N‐GO) by an in situ growth route. The array‐like colloid composite of NiCo III Fe‐LDH/N‐GO is used as a bifunctional catalyst for both oxygen evolution/reduction reactions (OER/ORR). The NiCo III Fe‐LDH/N‐GO array has a 3D open structure with less stacking of LDHs and an enlarged specific surface area. The hierarchical structure design and novel material chemistry endow high activity propelling O2 redox. By exposing more amounts of Ni and Fe active sites, the NiCo III Fe‐LDH/N‐GO illustrates a relatively low onset potential (1.41 V vs reversible hydrogen electrode) in 0.1 mol L −1 KOH solution under the OER process. Furthermore, by introducing high valence Co 3+, the onset potential of this material in ORR is 0.88 V. The overvoltage difference is 0.769 V between OER and ORR. The key factors for the excellent bifunctional catalytic performance are believed to be the Co with a high valence, the N‐doping of graphene materials, and the highly exposed Ni and Fe active sites in the array‐like colloid composite. This work further demonstrates the possibility to exploit the application potential of LDHs as OER and ORR bifunctional electrochemical catalysts. Abstract : NiCoFe‐layered double hydroxides with Co 3+ are vertically grown on N doped graphene oxide by an in situ growth route. The changing of electronic structure induced by N atoms, Co 3+, and highly exposed edge sites of NiCoFe‐LDH contribute together to the excellent OER and ORR performances of bifunctional catalyst.